Effect of Particle Size and Sintering Temperature on the Formation of Mullite from Kyanite and Aluminum Mixtures. (26th February 2021) - Barrientos-Hernández, F. R.; Pérez-Labra, M.; Lobo-Guerrero, A.; Reyes-Pérez, M.; Juárez-Tapia, J. C.; Hernández-Ávila, J.; Cardoso-Legorreta, E.; Hernández-Lara, J. P.
Abstract : The effect of particle size and sintering temperature of the mixtures of kyanite and metallic aluminum related to the thermal transformation of kyanite into primary mullite and free silica was studied. In addition, the reaction between α -Al2 O3 (in situ produced by aluminum oxidation) and the silica was obtained in cristobalite structure from kyanite to obtain secondary mullite. The kyanite powders were milled by 0.5, 3, 6, and 12 hours and then were mixed with aluminum powder, which were previously milled by 3 hours. After that, the powders were characterized by X-ray diffraction technique (XRD), scanning electronic microscopy (SEM), differential thermal analysis (DTA), and thermogravimetric analysis (TGA), and the particle size was determined in a centrifugal analyzer particle size Shimadzu model SA-CP4. The mixed powders were pressed uniaxially into cylindrical samples (compacts), and then sintering was conducted at 1100, 1200, 1300, 1400, 1500, and 1600°C; these samples were characterized by XRD, SEM, and thermodilatometry analysis (TD); density and open porosity measurements were performed by the Archimedes method. The samples were thermally etched to observe the microstructure, which consisted of mullite equiaxial grains contained in a glassy phase. It was observed that the nonmilled kyanite mineral becomes into mullite plus silica at temperatures between 1400 and 1500°C. When the particle size was reduced at sizes less than 1 µ m, the transformation temperature was low until 200°C; the X-ray patterns of the sintered samples at 1400°C, ground for 6 hours, showed mullite peaks with small reflections of cristobalite and α -Al2 O3, and these samples exhibited high density and low open porosity.